Making sense of the future: visions and transition pathways of laypeople and professionals from six EU countries - Iacovidou, A.; Wehrmeyer, Walter (-, 2015)
In seeking to understand how young people conceptualise their future in terms of sustainability, visioning and backcasting workshops were held in six European countries, as part of the CReating Innovative Sustainability Pathways (CRISP) project. Within the visioning part of the CRISP project, over 1500 ideas and suggestions were generated, which were then condensed into three pan-European archetypical visions: One Ethical World, Local Community and i-Tech that exhibit radical alternatives for global and local futures. For the transition pathway development of these futures, backcasting workshops were held with the participation of young people and experts to develop suitable pathways towards each of the three visions with regard to three specific sectors, namely, household energy, individual mobility and food. This paper presents the novel methodology developed and applied in both sets of workshops and describes the innovative approach followed for synthesising strong, coherent transition pathways. The framework of actions of each vision's pathway towards a sustainable, low-carbon Europe is also presented to provide the basis upon which changes towards a sustainable future can be initiated both at structural and practical levels. The paper concludes with an evaluation of the pathways developed by comparing them to the UK 2050 pathways.